FACTORS ASSOCIATED WITH LENGTH OF HOSPITAL STAY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE HOSPITALIZED FOR ACUTE EXACERBATION - Pham Duc Minh,; Dao Ngoc Bang, (Tạp chí Y học Quân sự, 2026)
Objective: To identify factors associated with length of hospital stay in patients with COPD hospitalized for acute exacerbation. Subjects and methods: A prospective cohort study was conducted on 58 patients with COPD admitted for acute exacerbation. Clinical characteristics, comorbidities, symptom burden assessed by the COPD Assessment Test (CAT), and nutritional status were assessed at hospital admission. As LOS showed a right-skewed distribution, a generalized linear model with Gamma distribution and log link was applied; results were expressed as Mean Ratios (MRs). Results: The median length of hospital stay was days (7-11 days). The patients were predominantly elderly men; the proportions of patients classified as COPD group D, with CAT ≥ 10, with comorbidities, and with malnutrition according to SGA-B/C were 55.2%, 81.0%, 60.3%, and 50.0%, respectively. Length of stay was positively correlated with the number of comorbidities, mMRC score, and CAT score. In the final reduced Gamma regression model, absence of comorbidities (MR = 0.79; 95% CI: 0.65-0.95; p = 0.012), CAT < 10 (MR = 0.76; 95% CI: 0.61-0.94; p = 0.014), and higher serum albumin concentration (MR = 0.97 per 1 g/L increase; 95% CI: 0.94-0.99; p = 0.007) were independently associated with shorter hospital stay. Conclusions: Length of hospital stay in patients with acute exacerbation of COPD was associated with symptom burden, comorbidities, and serum albumin concentration. Early assessment of symptoms and nutritional status is necessary for risk stratification and optimization of inpatient management.